If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(7x + 4) = 6(x + 2) Reorder the terms: 3(4 + 7x) = 6(x + 2) (4 * 3 + 7x * 3) = 6(x + 2) (12 + 21x) = 6(x + 2) Reorder the terms: 12 + 21x = 6(2 + x) 12 + 21x = (2 * 6 + x * 6) 12 + 21x = (12 + 6x) Add '-12' to each side of the equation. 12 + -12 + 21x = 12 + -12 + 6x Combine like terms: 12 + -12 = 0 0 + 21x = 12 + -12 + 6x 21x = 12 + -12 + 6x Combine like terms: 12 + -12 = 0 21x = 0 + 6x 21x = 6x Solving 21x = 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 21x + -6x = 6x + -6x Combine like terms: 21x + -6x = 15x 15x = 6x + -6x Combine like terms: 6x + -6x = 0 15x = 0 Divide each side by '15'. x = 0 Simplifying x = 0
| -8-k=-25 | | 35x^2-3=22x | | (8x-41)+(9x+17)=180 | | r-7=58 | | X-1+5=-15+16x-7 | | 5-x+1=2 | | X=259 | | 26-2b=-8 | | x=5/2=10 | | y-0.7x=12 | | 15*3-25+10=x | | -4-7x=1-6x | | (5n-1)(n+7)=0 | | 8-2(4x+9)=6x-4(m-5) | | 15-z=45 | | 9x+17=8x-41 | | -4y+8=-8y-12 | | 6x-6=14x-14 | | -14-r-6r=r+8 | | 2210=r(34) | | 42=2+6 | | 9-4b=6-5b | | 6-4(5+3y)=0 | | 8-1/2(-m-1) | | M+6=2m+11 | | 7v-15+7v=7v+48 | | 23=32x-425 | | 1680=336t | | 5(9x+6)=45x-4 | | 0.5x=-70 | | 3lx-1l=15 | | (3x+25)+(x-5)+x=180 |